Standardized assessment of cognitive function of post‐acute care patients. Issue 4 (2nd March 2022) - Shier, Victoria; Edelen, Maria O.; McMullen, Tara L.; Ahluwalia, Sangeeta C.; Chen, Emily K.; Dalton, Sarah E.; Paddock, Susan; Rodriguez, Anthony; Sherbourne, Cathy D.; Mandl, Stella; Mota, Teresa; Saliba, Debra
Abstract: Background: The assessment of cognitive function in post‐acute care (PAC) settings is important for understanding an individual's condition and care needs, developing better person‐directed care plans, predicting resource needs and understanding case mix. Therefore, we tested the feasibility and reliability of cognitive function assessments, including the Brief Interview for Mental Status (BIMS), Confusion Assessment Method (CAM©), Expression and Understanding, and Behavioral Signs and Symptoms for patients in PAC under the intent of the IMPACT Act of 2014. Methods: We conducted a national test of assessments of four standardized cognitive function data elements among patients in PAC. One hundred and forty‐three PAC settings (57 home health agencies, 28 inpatient rehabilitation facilities, 28 long‐term care hospitals, and 73 Skilled Nursing Facilities) across 14 U.S. markets from November 2017 to August 2018. At least one of four cognitive function data elements were assessed in 3026 patients. We assessed descriptive statistics, percent of missing data, time to complete, and interrater reliability between paired research nurse and facility staff assessors, and assessor feedback. Results: The BIMS, CAM©, Expression and Understanding, and Behavioral Signs and Symptoms demonstrated low rates of missing data (less than 2%), high percent agreement, and substantial support from assessors. The prevalence of Behavioral Signs and Symptoms was low in our sample of PAC settings. Conclusion: Findings provide support for feasibility of implementing standardized assessment of all our cognitive function data elements for patients in PAC settings. The BIMS and CAM© were adopted into federal Quality Reporting Programs in the fiscal year/calendar year 2020 final rules. Future work could consider implementing additional cognitive items that assess areas not covered by the BIMS and CAM©.